Effect of Liquidity and Debt Policy on The Financial Performance of PT. Ultrajaya Milk Industry & Trading Company, TBK. Period 2011-2021 - Wahyu Andri Wibowo; Angga Pratama; Devi Miftahul Karimah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2023)
This study aims to analyze the effect of liquidity and debt policy on financial performance at PT. Ultrajaya Milk Industry & Trading Company, Tbk during the 2011-2021 period. The research method used is descriptive quantitative using secondary data in the form of company financial reports. The analysis performed includes classical assumption tests, correlation analysis, coefficient of determination tests, multiple linear regression analysis, and hypothesis testing using SPSS version 25. The results showed that the liquidity ratio has a significant influence on financial performance, the debt to equity ratio does not have a significant effect on financial performance. Further analysis shows that together, liquidity and debt policy have a significant influence on financial performance. The variables studied explain about 13.8% of the variation in the rate of return on equity, while the rest is influenced by other factors not explained in this study. The resulting multiple regression equation is Y = 309229922.296 + 0.024x1 + 0.333x2 + e. The results of this study contribute to understanding the relationship between liquidity, debt policy, and company financial performance. The implication can assist management in making more informed decisions regarding liquidity management and debt policy in order to improve the company's financial performance.